Comparative Study of FE-models and Material Data for Fatigue Life Assessments of Welded Thin-walled Cross-beam Connections. (2015) - Gorash, Yevgen; Comlekci, Tugrul; MacKenzie, Donald
Abstract: This paper investigates the effects of fatigue material data and finite element types on accuracy of residual life assessments under high cycle fatigue conditions. The bending of cross-beam connections is simulated in ANSYS Workbench for three different combinations of structural member shapes: RHS-RHS, RHS-angle and RHS-Channel. The weldments are made of the structural steel grades C350LO and C450LO according to the Australian Standard AS3678. The stress analysis of each weldment having specific profile dimensions under specific cyclic loading is implemented using solid and shell elements considering linear material and geometric response. The stress results are transferred to the fatigue code nCode DesignLife for the residual life prediction. For both variants of FE-mesh, the nominal stress in the weld toes is extracted by splitting the total stress into membrane and bending components and filtering out non-linear component. Considering the effects of mean stress, bending and thickness according to BS7608, failure locations and fatigue life are predicted using the Volvo method and stress integration rules from ASME Boiler & Pressure Vessel Code. Three different pairs of S-N curves (stiff for pure tension and flexible for pure bending) are considered in this work including generic seam weld curves from nCode DesignLife and FE-Fatigue and curves for the Japanese steel JIS G3106- SM490B, which is an equivalent with properties in between C350LO and C450LO. The numerical predictions are compared to the available experimental results highlighting the most preferable fatigue data input and FE-model formulation.